(untitled) (Journal on studies and research of academic knowledge, 2021)
This study aims to describe the psychological and pedagogical conditions of higher education students to face training under the distance modality in the context of the COVID-19 virus pandemic. The methodology responds to the quantitative, non-experimental, cross-sectional, descriptive approach. Data collection was carried out by applying a closed questionnaire, the sample consisted of 426 students. The type of sampling was non-probabilistic, by chain samples or by networks. The findings demonstrate that the Covid-19 pandemic emotionally affected most of the population surveyed during the pandemic, flourishing attitudes such as anxiety, frustration, tiredness, lack of motivation, boredom, yet they adopted measures of emotional restraint and developed soft skills. In general, they have the necessary technological resources, as well as the physical spaces and skills for the development of virtual classes; however, they find it difficult to understand the didactic guides and consider the work carried out by the teachers to be extensive. Likewise, a minority population has been found that does not have the conditions required for the development of distance education.